(untitled) (The Research of Medical Science Review, 2025)
Background: Nursing is still a female-dominated field, and male nursing learners frequently meet with special challenges in clinical practice. Those gender-based problems may influence their learning, identity, and even emotional well-being in clinical contexts. Aim: The aim of this study was to explore and understand the lived experiences of male nursing students placed in female-dominated clinical environments. Methods: To develop profound understanding of the personal experiences of the male students, a qualitative phenomenological design was employed. The study was conducted at Saidu Teaching Hospital, Swat. Purposive sampling was conducted to select 12 final-year male nursing students. Face-to-face interviews were semi structured and conducted in a confidential area. Interviews lasted 45–60 minutes and were audio-recorded with consent. Thematic analysis was used to analyze data with major themes generated using coding, categorization, and member checking to achieve credibility. Results: Five key themes were identified: stereotyping of roles based on genders, a sense of isolation, inadequate mentorship and representation of males in the workplace, a struggle with professional identity, and resilience and coping mechanisms. Participants stated that they received physical assignments, social exclusion, and did not receive gender-specific mentorship. In spite of these obstacles, the students showed resilience especially through sharing peer bonds, objective end setting, and inner drive. Conclusion: These results point to a need to create gender-sensitive clinical training arrangements to accommodate male students by providing equal task assignment, inclusive mentorship, and identity formation. By doing so, the problems facing male students can be improved, and their retention increased, as well as the diversity of the nursing workforce